Efficacy of prenatal diagnostic in mothers of children with chromosomal aberrations diagnosed postnatally - Yu.A. Dudareva; A.A. Shipilov (LCC «Medicine-Inform», 2021)
Yu.A. Dudareva1, A.A. Shipilov2 1Altay State Medical University, Barnaul, Russian Federation 2Altay Regional Clinical Perinatal Center, Barnaul, Russian Federation Aim: to assess the efficacy of prenatal screening in women those children were diagnosed with chromosomal aberrations postnatally. Patients and Methods: this descriptive cross-sectional retrospective study was performed to analyze medical records, obstetric gynecological database, and the results of prenatal screening in women (Altay Region residents) who gave birth to children with chromosomal aberrations in 2017-2019. The examination also included the calculation of the individual risk of fetal chromosomal aberrations using Astraia and PRISCA software. Results: in 2017-2019, sixty-nine children with chromosomal aberrations were born in the Altay Region. Most (90%) children were diagnosed with Down's syndrome. More girls were born than boys (1.7:1). The mean age of women who gave birth to children with chromosomal aberrations diagnosed postnatally was 35 years. In 4.3%, mean mother's age was 21.3 years. In 40.6%, mean mother's age was 31.2 y ears. Every second woman (55.1%) was older than 35 years. A retrospective analysis of pathological prenatal markers and automated calculation of individual risk have demonstrated that the risk of fetal chromosomal aberrations was moderate to high in 79.7%. In this risk score, the diagnosis can be verified prenatally. Sonographic and biochemical markers of fetal chromosomal aberrations were lacking in 20.3%. Early prenatal screening was not performed in 20.3% due to late referral to the maternity clinic. Sonographic markers, diagnosed congenital anomalies, and biochemical tests in the second trimester were the most effective prenatal markers of chromosomal aberrations. Conclusions: following the technology of prenatal screening to identify fetal chromosomal aberrations allows for verifying the diagnosis and granting the families the right to decide on the utility to prolong pregnancy. Keywords: prenatal screening, chromosomal aberrations, congenital anomalies, karyotyping, genetic counseling, noninvasive prenatal testing. For citation: Dudareva Yu.A., Shipilov A.A. Efficacy of prenatal diagnostic in mothers of children with chromosomal aberrations diagnosed postnatally. Russian Journal of Woman and Child Health. 2021;4(1):42-45. DOI: 10.32364/2618-8430-2021-4-1-42-45.